2006
DOI: 10.1590/s1516-89132006000600020
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavones in processed soybean products from Ecuador

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…Lemos et al (2004) found that in Farfantepenaeus paulensis, soybean meal exhibited reduced digestibility and a high degree of protease inhibition. The occurrence of trypsin inhibitor can be attributed to insufficient heat during processing (Swick, 2000, Genovese et al, 2006. Since the ingredients tested were obtained from the feed manufacturers, the poor digestibility observed for soybean meal in A. longinaris would be a reason to increase the quality control of this feedstuff prior to use in shrimp feeds.…”
Section: Resultsmentioning
confidence: 99%
“…Lemos et al (2004) found that in Farfantepenaeus paulensis, soybean meal exhibited reduced digestibility and a high degree of protease inhibition. The occurrence of trypsin inhibitor can be attributed to insufficient heat during processing (Swick, 2000, Genovese et al, 2006. Since the ingredients tested were obtained from the feed manufacturers, the poor digestibility observed for soybean meal in A. longinaris would be a reason to increase the quality control of this feedstuff prior to use in shrimp feeds.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the 4'- Total isoflavone content in whole soy usually ranges from 50 to 450 mg/100 g dried weight (Kim et al 2005). Generally, the -glucosides account for the 30-35%, the 6"-O-malonyl--glucosides are the most abundant (50-65%), the aglycone content is less important (4-12%) and the 6"-O-acetyl--glucosides are usually scarce (0-5%) (Franke et al 1999;Genovese et al 2006). These percentages may change significantly when soy is processed since the 6"-Omalonyl--glucosides are instable under heat so that they are converted into the corresponding aglycones (Villares et al 2011).…”
Section: Isoflavonesmentioning
confidence: 99%
“…In eighteen different soybean genotypes, they found the total isoflavone levels ranging from 0.9 to 1.21 mg/g of the seed. Genotype from Ecuador had 0.68 mg of total isoflavones per g of the seed, which is in the range of Brazilian genotypes, but far below isoflavone content in American and Korean genotypes (Genovese et al, 2006). The average total isoflavone content in Indian seeds, according to the study by Devi and collaborators (2009), was 0.76 mg/g of the seed.…”
mentioning
confidence: 91%